Farm Laborer Households from a Survival Strategy Perspective (A Case Study in Tempuran Village, Paron Subdistrict, Ngawi, Indonesia) - Khusnul Ikhriyah Nur Aini; Nuriah Yuliati; Risqi Firdaus Setiawan (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
Farm laborer households are economically vulnerable due to limited access to land and unstable incomes. This situation puts most farm laborer households in Tempuran Village under high economic pressure. Tempuran Village is an agricultural area where most residents depend on the agricultural sector, but many of them do not own land and therefore work as seasonal farm laborers with fluctuating incomes. This study aims to analyze the level of poverty experienced and survival strategies employed by farm laborers' households in Tempuran Village. This study was conducted in Tempuran Village, Paron Subdistrict, Ngawi District, using a mixed-methods approach, namely in-depth interviews and poverty line calculations from the Central Statistics Agency (BPS) 2025, set at IDR 445,865 per capita per month. Data was obtained from 58 farm laborer households. The results of the study indicate that 76.8% of farm laborer households in Tempuran Village are classified as poor, consisting of 12.1% in the poorest category (n=7), 75.8% in the poor category (n=44), and 12.1% in the vulnerable category (n=7). Their average per capita income is only Rp 323,678 per month, reflecting limited access to economic resources and low capacity to meet basic needs. To survive economic pressures, farm laborer households use three main strategies: active strategies (seeking additional work in both agricultural and non-agricultural sectors), passive strategies (reducing consumption and selling assets), and network strategies (utilizing government social assistance or support from family and the surrounding community). Of the 58 respondents, 62.1% implemented active strategies, 58.6% implemented passive strategies, and 77.6% implemented network strategies. Network strategies were the most dominant Strategy, indicating that most households relied on social support to cover income shortfalls. The findings of this study suggest that village governments and social service institutions should design targeted assistance programs.